Delayed Presentation and Mortality in Children With Sepsis in a Public Tertiary Care Hospital in Tanzania - Smith, Audrey Marilyn; Sawe, Hendry R.; Matthay, Michael A.; Murray, Brittany Lee; Reynolds, Teri; Kortz, Teresa Bleakly (Frontiers in Pediatrics, 2021)
Title: Delayed Presentation and Mortality in Children with Sepsis in a Public Tertiary Care Hospital in Tanzania Authors: Smith AM, Sawe HR, Matthay MA, Murray BL, Reynolds TA, Kortz TB Background: Over 40% of the global burden of sepsis occurs in children under five years of age, making pediatric sepsis the top cause of death for this age group. Prior studies have shown that outcomes in children with sepsis improve by minimizing the time between symptom onset and treatment. This is a challenge in resource-limited settings where access to definitive care is limited. Methods: A secondary analysis was performed on data from 1803 patients (28 days – 14 years old) who presented to the emergency department (ED) at Muhimbili National Hospital (MNH) from July 1, 2016 to June 30, 2017 with a suspected infection and ≥ 2 clinical systemic inflammatory response syndrome criteria. The objective of this study was to determine the relationship between delayed presentation to definitive care (>48 hours between fever onset and presentation to the ED) and mortality, as well as the association between socioeconomic status (SES) and delayed presentation. Multivariable logistic regression models tested the two relationships of interest. We report both unadjusted and adjusted odds ratios and 95% confidence intervals. Results: During the study period, 11.3% (n=203) of children who presented to MNH with sepsis died inhospital. Delayed presentation was more common in non-survivors (n=90/151, 60%) compared to survivors (n=614/1353, 45%) (p≤0.01). Children who had delayed presentation to definitive care, compared to those who did not, had an adjusted odds ratio for mortality of 1.85 (95% CI: 1.17 - 3.00). Conclusions: Delayed presentation was an independent risk factor for mortality in this cohort, emphasizing the importance of timely presentation to care for pediatric sepsis patients. Potential interventions include more efficient referral networks and emergency transportation systems to MNH. Additional clinics or hospitals with pediatric critical care may reduce pediatric sepsis mortality in Tanzania, as well as parental education programs for recognizing pediatric sepsis.